Cultural and Scientific Relations between the Soviet Union and Egyptian Jews (1922 – 1935) - Shahab, Nuha Abd Almanam; Al-Obaidi, Anas Abd Alkhaleq Ayed; Al-Jubouri, Ahmed Hussein Abed (Journal of Ecohumanism, 2025)
The vital role played by the All-Union Association for Cultural Relations reflected the strengthening of ties between the Soviet Union and the Jews of Egypt. These ties were not limited to the exchange of cultural knowledge only, but also included the exchange of scientific and technical knowledge that had a significant impact on the development of important sectors such as agriculture and industry. This cooperation, which was part of the strategies of the Zionist project, sought to exploit Soviet technologies to achieve progress in these fields. The interest of the Jews in Egypt in Soviet cultural, social and political programs also reflected the growing influence of Soviet ideology at that stage. Through cultural associations, the Soviets sought to expand their cultural and social influence among Jewish communities in various countries, which highlights the role of culture as a diplomatic and expansionist tool during that period.